Urgensi Pendidikan Multikultural di Sekolah Inklusi Dalam Menghargai Toleransi Keberagaman - Aeni, Nur; Ida Hidayatu Solelah; Nurul Mubin (Al Jabiri: Jurnal Ilmiah Studi Islam, 2024)
Indonesia is known as a country rich in cultural, ethnic, religious, linguistic, and social diversity. This diversity is both a strength and a challenge that requires effective management, particularly in the field of education. Multicultural education in inclusive schools plays a crucial role in instilling values of tolerance and appreciation for diversity. Inclusive schools, designed to accept students from various backgrounds and needs, serve as a strategic platform for integrating multicultural education. This article aims to examine the urgency of implementing multicultural education in inclusive schools through a literature study approach. The findings indicate that the implementation of multicultural education can be carried out through various strategies, such as inclusive curricula, intercultural dialogue, collaborative learning, diverse teaching staff, diversity-based extracurricular activities, cross-cultural interactions, the use of technology, and creating a safe environment. However, this implementation faces challenges such as limited teacher understanding, lack of resources, prejudice, and insufficient family support. Proposed solutions include teacher training, provision of adequate resources, and collaboration between schools and families. With the right steps, multicultural education in inclusive schools can contribute to the formation of a tolerant, inclusive generation capable of living harmoniously in a multicultural society.